Using Video Recording Task to Improve English Speaking Skills of Students at Management Program - Andhina Ika Sunardi; Agnes Nora Eko Wahyu Utami; Herman Wahyu Dwi Maelana (Siliwangi University, 2023)
The main goal of this research is to develop learning method which can improve the speaking skills of students at Management Program by implementing video recording tasks. This research is Research and Development (RD) research employing the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) Model. The respondents in this study were 30 students who took part in English I subject of Management Program. The instruments used in this study were speaking evaluation sheet, questionnaires, and semi-structured interviews. The research data was obtained from their responses to the questionnaire given related to the use of video recording tasks to improve the English-speaking skills of the students at Management study program. From the results of the study, it can be concluded that using a task-based approach to video recording can effectively help students improving their speaking skills. This can be shown that fluency, vocabulary, grammatical structure and pronunciation have P value lower than 0,05, meaning that those variables significantly support the use of video recording task to improve students speaking skills. Besides, students express their pleasure and positive perception of the method. In conclusion, the use of task-based video recording methods can effectively help students improve their oral skills, not only for exams, but also for their real life and future needs. Additionally, students express their pleasant and positive views on this method. Keywords: English Language, Speaking Skill, Video Recording Task